SELF-CONCEPT OF GIFTED CHILDREN: QUALITATIVE RESEARCH - Nur Rahmawati, Ajeng Intan; Ariffudin, Imam (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
This research aims to examine and analyze in depth the self-concept of gifted children. Self-concept is an individual's frame of reference for behavior that originates from internal socialization. This research uses a qualitative phenomenological approach. The subjects in this research were three people, and the data collection process was through interviews, observation and documentation. The results of the research show that gifted children have a self-concept, namely they like being a leader, have a high sense of curiosity, are critical, and sensitive, and have anxiety between their real self and their ideal self . Other things could be studied in further research regarding perfectionism in gifted children.